2014
DOI: 10.1177/1535370214549521
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid affects the oxidative stress in various brain structures in mice with methionine and choline deficiency

Abstract: Deficiency in methionine or choline can induce oxidative stress in various organs such as liver, kidney, heart, and brain. This study was to examine the effects of alpha-lipoic acid (LA) on oxidative stress induced by methionine and choline deficiency (MCD) in several brain structures. Male mice C57BL/6 (n ¼ 28) were divided into four groups: (1) control -continuously fed with standard chow; (2) LA -fed with standard chow and receiving LA; (3) MCD2 -fed with MCD diet for two weeks, and (4) MCD2þLA -fed with MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Studies performed using in vivo and in vitro showed that ALA can prevent stress oxidative by inducing of enzymatic antioxidant activity (SOD, catalase and GSH) as well as enhancing the capacity of free radical scavenging and by blocking lipid peroxidation (Abdou and Abdel-Daim 2014;Castro et al 2014;Gorąca et al 2013;Xia et al 2014). Because of its antioxidant activity, ALA acts as a neuroprotective agent in various neurodegenerative diseases related to stress oxidative stress (Boyaci et al 2014;Dalazen et al 2014;Demir et al 2014;Jalali-Nadoushan and Roghani 2013;Li et al 2013;Veskovic et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Studies performed using in vivo and in vitro showed that ALA can prevent stress oxidative by inducing of enzymatic antioxidant activity (SOD, catalase and GSH) as well as enhancing the capacity of free radical scavenging and by blocking lipid peroxidation (Abdou and Abdel-Daim 2014;Castro et al 2014;Gorąca et al 2013;Xia et al 2014). Because of its antioxidant activity, ALA acts as a neuroprotective agent in various neurodegenerative diseases related to stress oxidative stress (Boyaci et al 2014;Dalazen et al 2014;Demir et al 2014;Jalali-Nadoushan and Roghani 2013;Li et al 2013;Veskovic et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Though earlier studies [ 45 , 46 ] have shown AlCl 3 to inhibit catalase activity in rat brain, in the present study there was an increase in brain catalase activity in AlCl 3 treated rats. This variation may be explained by differential effects of oxidative stress on catalase activities in various regions of brain [ 47 ]. Studies of Singla and Dhawan 2014 [ 48 ] have shown that AlCl 3 causes an increase in catalase activity in rat brain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that lipoic acid may cross the blood brain barrier, reduce MDA formation and enhance the activity of brain catalase and other antioxidant enzymes (Veskovic et al, 2015). In addition, lipoic acid is a thiol compound that possesses direct free radical scavenging activity (Shila et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%